Advances in animal models of obstructive sleep apnea - Zong, Shimin; Du, Peiyu; Li, Hejie; Wang, Miao; Xiao, Hongjun (Frontiers in Medicine, 2023)
Animal experiments play an important role in the study of the pathogenesis of human diseases and new methods of diagnosis and treatment. Due to the great differences in the anatomical structure and physiology of the upper airway between animals and humans, there is currently no animal model that can fully simulate the pathological anatomy and pathophysiological characteristics of human obstructive sleep apnea (OSA) patients. Herein, we summarizes the construction methods of several OSA animal models that have been widely used in the studies published in the last five years, the advantages and limitations of each model as well as related evaluation techniques are described. This information has potential to provide further guide for the development of OSA related animal experiments.